PENGARUH EKSTRAKURIKULER KLUB DEBAT SMANSA (KDS) TERHADAP KARAKTER CINTA TANAH AIR PADA SISWA DI SMA NEGERI 1 PEKANBARU - Ryade Deantara; Hambali Hambali; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This research is motivated since FKIP Riau University held competitions such as the Olympics, making Pekanbaru 1 High School students motivated to continue to try to participate in the debate competition activities held by FKIP Riau University through its Olympic Event and even student activities are fully supported by the school. This research was conducted at SMA Negeri 1 Pekanbaru. A series of activities were carried out in November 7 to 22 November 2019. The population and sample were 40 people. Data analysis techniques using quantitative descriptive analysis. The results showed that the percentage of respondents obtained answers to the extracurricular influence of the Smansa Debate Club (KDS) on the character of Cinta Tanah Air in the students of SMA Negeri 1 Pekanbaru. The extracurricular variables of the Smansa Debate Club (variable 1) who answered strongly agreed amounted to 79.5% plus the results of the calculation of respondents who answered Agree amounted to 20% namely the sum of 99.5%, where the very high range is at 75.01% -100% . Thus it can be concluded that the influence of the Smansa Debate Extracurricular on the Love of the Fatherland character of SMA Negeri 1 Pekanbaru students is at a Very High level. Furthermore, the character variable Cinta Tanah Air in SMA Negeri 1 Pekanbaru is included in both categories. This is because the results of strongly agree answers amountedto 88.25% added to the agreed answers amounted to 11.28% amounting to 100.03%. It can be concluded that the character of Cinta Tanah Air in the extracurricular activities of the Smansa Debate Club in SMA Negeri 1 Pekanbaru is included in the Very High category.KeyWords : Character Of Cinta Tanah Air, Klub Debat Extracurricular